(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the theoretical foundations and practical dimensions of corrective speech therapy work with school-aged children diagnosed with dyslalia and dysarthria. Drawing on contemporary scientific literature and clinical practice, the study analyzes the etiological causes of these disorders, their clinical and pedagogical characteristics, evidence-based diagnostic methods, and effective corrective intervention strategies. Particular attention is given to the necessity of individualized treatment planning, systematic articulation gymnastics, the development of phonemic awareness, multidisciplinary collaboration among specialists, and the critical role of psychological support in optimizing children’s communicative competence. The article underscores that early and targeted intervention not only corrects speech defects but also substantially improves academic achievement and social integration in school-aged populations.